The Indonesian Capital Market's Reaction to the Decision Regarding the Announcement of the Large-Scale Social Restrictions - Fitria, Nida; Damayanti, Cacik Rut (FIA UB, 2023)
The announcement of the first PSBB decision is a non-economic event that can affect stock price movements. Signaling theory is the basis of this research. The latest information signals that the regional quarantine announcement can affect the stock price index movement in the capital market. Abnormal returns and trading volume activity are indicators that measure the reaction rate of a stock in the capital market. This study aims to determine whether there is an average abnormal return and trading volume activity before and after the announcement of the PSBB decision. This research is an event study that studies the market reaction with a quantitative approach. The population and sample in this study are company stocks listed on the LQ45 index for February - July 2020 using the Purposive Sampling technique. The research period is five days before and after the event (a total of ten days). The hypothesis test used is the Wilcoxon Signed Rank Test. The result was differences in abnormal returns before and after the event. The Wilcoxon signed rank test results on the trading volume activity variable did not find any significant difference in trading volume before and after the announcement regarding the initial PSBB decision.